PREPARTUM PROLAPSE OF GRAVID UTERINE CORNUA ALONG WITH RECTAL PROLAPSE AND ITS MANAGEMENT IN A DOE - B. Bibin Becha; M.P. Unnikrishnan; Lakshmi Bhai; Sunita Behera (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 1½ year old Malabari doe in its 120 day old first gestation was presented with a complaint of cervico-vaginal and rectal prolapse which was already attended by a Veterinarian. On examination the case was diagnosed to be prepartum prolapse of gravid horn of uterus along with rectal prolapse. The condition was successfully managed by relieving one fetus from the prolapsed horn by hysterotomy, replacing the uterine horn and suturing the vaginal tear. Buhner’s and purse string sutures were applied after correcting cervico-vaginal and rectal prolapse, respectively. The other twin fetus from opposite horn was relieved by caesarean section. The animal had an uneventful recovery.